The use of loose salt for fattening pigs in the dry lot. - Aubel, C.E. (Kansas Agricultural Experiment Station, 2012)
At the Livestock Feeders' Day last year, data were presented on the use of loose salt in swine fattening rations when the pigs were self-fed free choice a ration of shelled corn, tankage, and alfalfa hay. It was shown that loose salt, self-fed to pigs provided no advantage in producing faster gains or in improving the efficiency of the rat ion. In the test reported on last year the entire protein supplement, aside from the alfalfa was of animal protein. Since present-day hog supplements are largely mixtures of plant and animal protein feeds, it was thought that information would be desirable on the influence of feeding salt when a supplement of such a composition was fed.
Keywords: Swine; Salt; Dry lot; Gain